A new genus and species of the family Microlaimidae (Nematoda: Chromadorea) from intertidal sand of the Jeju Island, South Korea - Tchesunov, Alexey V.; Jeong, Raehyuk; Lee, Wonchoel (Zootaxa, 2021)
As a part of the study of marine nematofauna of a sandy intertidal zone of Jeju Island (South Korea), a number of species have been proven as new for science. Here a new species representing a new genus of the family Microlaimidae (Chromadorea), Jejulaimus sinyangensis gen. n., sp. n. is described. The new monotypic genus is characterized by head set off abruptly from the body; anterior sensilla pattern 6+10, where six outer labial setiform sensilla together with four longer cephalic setiform sensilla are integrated in a common crown; pharyngostoma armed with a dorsal tooth and surrounded by convex muscular pharyngeal tissue, forming an anterior pharyngeal bulb which is distinctly set off from the rest of the pharynx; terminal pharyngeal bulb oval; ventral pore and ampulla of the excretory-secretory gland situated just posterior to the nerve ring; an only anterior testis present. The new genus bears some resemblance to the genera Bolbolaimus, Pseudomicrolaimus and Spirobolbolaimus in having an anterior pharyngeal bulb and in the position of the ventral pore of the excretory/secretory gland, but differs from them by anterior sensilla pattern 6+10, absence of subventral teeth in buccal cavity, and monorchic condition of male reproductive system.